2008
DOI: 10.1016/j.biomaterials.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica nanoparticle-modified surfaces on cell morphology, cytoskeletal organization and function

Abstract: Chemical and morphological characteristics of a biomaterial surface are thought to play an important role in determining cellular differentiation and apoptosis. In this report, we investigate the effect of nanoparticle (NP) assemblies arranged on a flat substrate on cytoskeletal organization, proliferation and metabolic activity on two cell types, Bovine aortic endothelial cells (BAECs) and mouse calvarial preosteoblasts (MC3T3-E1). To vary roughness without altering chemistry, glass substrates were coated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
131
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 42 publications
(39 reference statements)
11
131
0
1
Order By: Relevance
“…Because macromolecules are in a state of high entropy, and entropy is a statistical measure of randomness, the roughness presented by macromolecules is expected to be stochastic (random). We simulated random ECM nanoroughness using an assembly of monodispersed silica colloids of increasing size (10,24) (Fig. 1A).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Because macromolecules are in a state of high entropy, and entropy is a statistical measure of randomness, the roughness presented by macromolecules is expected to be stochastic (random). We simulated random ECM nanoroughness using an assembly of monodispersed silica colloids of increasing size (10,24) (Fig. 1A).…”
Section: Significancementioning
confidence: 99%
“…However, developmental processes such as axon pathfinding, synapse formation, nervous system patterning, neuronal plasticity, and degeneration fail to be explained solely on the basis of soluble factors. There is increasing evidence that physical variables such as the stiffness of a cellular environment influence cell development (7)(8)(9)(10)(11)(12). However, the cells of the brain tissue reside in a soft environment that is rich in polysaccharides (13,14).…”
mentioning
confidence: 99%
“…Alternatively, several categories of particulate materials have been explored for the nanomorphological modification of scaffold surfaces (bottom-up approach), including ceramics, polymers and nanotubes (19,20,21,22) . Particle-based surface decoration is highly promising since it is less dependent on the chemical nature of the scaffold material in contrast to lithographical modification.…”
Section: Engineering Scaffold Topographymentioning
confidence: 99%
“…ECM provides nanoscale structures, such as the 15-300 nm in diameter collagen fibrils that allow cell adhesion (via integrins) and immobilization of signaling molecules, thus influencing the fate and behavior (i.e., proliferation, migration and differentiation) of stem cells [107]. The concentration, size, spacing, surface chemistry and shape (e.g., ridges, grooves, pores and pits) of the artificial nanostructures (e.g., nanotubes and nanolines) are important parameters for the development of cell adhesion sites that monitor stem cell behavior [108][109][110]. For example, it has been shown that surface irregularity (e.g., nanoline grating) and diverse surface chemistries (e.g., silica and poly[methyl methacrylate]) are capable of enhancing adhesion, alignment, growth and differentiation of stem cells [108,109].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%